2022
DOI: 10.1007/s40123-022-00625-5
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Cell Loss in the Course of Central Serous Chorioretinopathy

Abstract: Introduction: Central serous chorioretinopathy (CSCR) as a clinical entity is potentially damaging and may significantly affect retinal morphology and function, especially in the chronic form. Our study aimed to determine the amount of deficit of best corrected visual acuity (BCVA) and individual retinal layers, including ganglion cells, in different types of CSCR and with reference to its duration. Methods: The retrospective analysis included 69 eyes of patients with resolved CSCR managed in Dobry Wzrok Ophth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…However, their sample size was small (n = 7), and their study cohort included both those who underwent laser treatment (n = 3) and those who were merely observed (n = 4), and they did not elaborate on the reasons for the reduction in GCL and RNFL thickness. Two previous studies align with our findings [7,8]. Gawecki et al [8] reported no significant differences in GCL-IPL thickness between acute CSC patients (n = 13) and a normal control group, while they noted a reduced GCL-IPL thickness in chronic CSC patients compared to controls.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, their sample size was small (n = 7), and their study cohort included both those who underwent laser treatment (n = 3) and those who were merely observed (n = 4), and they did not elaborate on the reasons for the reduction in GCL and RNFL thickness. Two previous studies align with our findings [7,8]. Gawecki et al [8] reported no significant differences in GCL-IPL thickness between acute CSC patients (n = 13) and a normal control group, while they noted a reduced GCL-IPL thickness in chronic CSC patients compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…Two previous studies align with our findings [7,8]. Gawecki et al [8] reported no significant differences in GCL-IPL thickness between acute CSC patients (n = 13) and a normal control group, while they noted a reduced GCL-IPL thickness in chronic CSC patients compared to controls. They surmised that chronic CSC patients experience loss of both the outer retinal layers and GCL, leading to significant visual impairment [8].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations